Chemopreventive Effects of Dietary Isothiocyanates in Animal Models of Gastric Cancer and Synergistic Anticancer Effects With Cisplatin in Human Gastric Cancer Cells - Rabben, Hanne-Line; Kodama, Yosuke; Nakamura, Masahiko; Bones, Atle Magnar; Wang, Timothy Cragin; Chen, Duan; Zhao, Chun-Mei; Øverby, Anders (Frontiers in Pharmacology, 2021)
Naturally occurring isothiocyanates (ITC) from edible vegetables have shown potential as chemopreventive agents against several types of cancer. The aims of the present study were to study the potential of ITC in chemoprevention and in potentiating the efficacy of cytotoxic drugs in gastric cancer treatment. The chemoprevention was studied in chemically induced mouse model of gastric cancer, namely N-methyl-N-nitrosourea (MNU) in drinking water, and in a genetically engineered mouse model of gastric cancer (the so-called INS-GAS mice). The pharmacological effects of ITC with or without cisplatin were studied in human gastric cell lines MKN45, AGS, MKN74 and KATO-III, which were derived from either intestinal or diffused types of gastric carcinoma. The results showed that dietary phenethyl isothiocyanate (PEITC) at a dose of 3-5 μmol/g diet reduced the tumor size only in mice when PEITC was given simultaneously with MNU, but showed no effect if administrated after MNU, or in INS-GAS mice. Treatment of gastric cancer cells with PEITC (1-100 μM) and cisplatin (5-200 μM) separately resulted in time- and dose-dependent inhibition on cell proliferation. When gastric cancer cells were pre-treated with PEITC for 1, 3 or 24 hrs at 10 and 20 μM, respectively, a time-and dose-dependent synergistic effects was observed when combined with cisplatin. The synergistic effect was not obtained when PEITC and cisplatin were given simultaneously, or when cisplatin was replaced by 5-fluorouracil. Furthermore, PEITC (10 and 20 μM) depleted glutathione by 66 and 91%, respectively, after only 3 hrs of treatment and induced G2/M cell cycle arrest. In conclusion, the results of the present study showed that PEITC displayed anti-cancer effects, particularly when given before the tumor initiation, suggesting a chemopreventive effect in gastric cancer, and that PEITC potentiated the anti-cancer effects of cisplatin, possibly by reducing the intracellular pool of glutathione and inducing cell cycle arrest suggesting a possible combination treatment of mono-chemotherapy plus PEITC.